Two maize END-1 orthologs, BETL9 and BETL9like, are transcribed in a non-overlapping spatial pattern on the outer surface of the developing endosperm - Joaquín eRoyo; Elisa eGomez; Olivier eSellam; Denise eGerentes; Wyatt ePaul; Gregorio eHueros (Frontiers in Plant Science, 2014)
In the course of a project aimed to isolate transfer cells-specific genes in maize endosperm we have identified the BETL9 gene. BETL9 encodes for a small protein very similar in sequence to the product of the barley transfer cell-specific gene end-1. Both BETL9 and END-1 proteins are lipid transfer proteins, but their function is currently unknown. In situ hybridization analysis confirms that the BETL9 gene is exclusively transcribed in the basal endosperm transfer cell layer during seed development since 10 days after pollination. However, immunolocalization data indicates that the BETL9 protein accumulates in the maternal placento-chalaza cells located just beside the transfer cell layer. This suggests that the BETL9 protein should be transported to the maternal side to exert its, still unknown, function. In addition, we have identified a second maize gene very similar in sequence to BETL9 and we have named it BETL9like. In situ hybridization shows that BETL9like is also specifically transcribed in the developing maize endosperm within the same time frame that BETL9, but in this case it is exclusively expressed in the aleurone cell layer. Consequently, the BETL9 and BETL9like genes are transcribed in a non-overlapping pattern on the outer surface of the maize endosperm. The BETL9 and BETL9like promoter sequences, fused to the GUS reporter gen, accurately reflected the expression pattern observed for the genes in maize. Finally, we have identified in the Arabidopsis genome a set of four genes orthologous to BETL9 and BETL9like and analysed the activity of their promoters in Arabidopsis transgenic plants carrying fusions of their promoter sequences to the GUS reporter. As in the case of the maize genes, the Arabidopsis orthologs showed highly complementary expression patterns.